Effectiveness of flutter-based piezoelectric energy harvesters with the presence of freeplay and aerodynamic nonlinearities - Bouma, Adam; Vasconcellos, Rui [UNESP]; Abdelkefi, Abdessattar (American Institute of Aeronautics and Astronautics (AIAA), 2022)
An investigation on the effects of the freeplay nonlinearity in the pitch degree of freedom on the behavior of a two-degree of freedom piezoaeroelastic energy harvesting system is investigated with simultaneously considering the stall nonlinearity. The aerodynamic loading used in this study is the unsteady representation, based on the Duhamel formulation. Nonlinear piezoaeroelastic response analysis is carried out in the presence of freeplay combined with structural nonlinearities before and after the linear onset of flutter. Such nonlinearities must be considered in the modeling and design of piezoaeroelastic energy harvesters, the combination of it can result in the presence of several secondary bifurcations and multiple solution regions and, therefore, affect the overall efficiency of the system. It is shown that the existence of freeplay nonlinearity leads to the possibility of harvesting energy at lower speeds than the linear onset speed of instability.